Transcriptome differentiation in Cryptomeria japonica trees with different origins growing in the north and south of Japan - Tokuko Ujino-Ihara; Kentaro Uchiyama; Seiichi Kanetani; Yoshihisa Suyama; Yoshihiko Tsumura (PLoS ONE, 2025)
Cryptomeria japonica is a coniferous species widely distributed throughout Japan and is therefore adapted to a variety of environments. To identify genes involved in its local adaptation, individuals of different origins growing in three common gardens located in the southern, central, and northern regions of Japan were subjected to transcriptome analysis. A transcriptome assembly guided by the whole-genome sequence of C. japonica yielded 77,212 transcripts derived from 56,203 genes. Based on single nucleotide polymorphisms (SNPs) detected in the transcriptome data, individuals were grouped into three genetic clusters. A total of 151 SNPs associated with population differentiation were detected using pcadapt. Of these, the allele frequencies of 40 SNPs showed associations with climatic variables, and the expression levels of genes containing 9 of these SNPs were also correlated with climatic variables. To further explore transcriptomic patterns underlying adaptation, weighted gene co-expression network analysis identified 25 gene modules. A comparison between representative expression patterns of each gene module and the genetic differentiation predicted by SNPs revealed that one module exhibited a negative correlation and another a positive correlation across all three common gardens. While defense response genes were highly expressed in individuals from the Pacific Ocean side of Japan (omote-sugi), terpenoid metabolism genes were more highly expressed in individuals from the Sea of Japan side (ura-sugi). These findings suggest that local adaptation in C. japonica involves not only responses to abiotic stress but also a significant contribution from genes involved in responses to biotic stress.